The Role of BNPL application in Boosting Consumer Purchasing Power During Economic Downturns: An Analytical Review and Strategic Implications - Jaelani, Abdul Qadir; Pradana, Mahir (Journal of Management World, 2025)
This study explores the influence of Buy-Now-Pay-Later (BNPL) application on consumer purchasing power during economic downturns. By providing a buy-now-pay-later option, BNPL application offers consumers financial flexibility that is particularly crucial in times of economic uncertainty. The research employs both quantitative and qualitative methods to analyze data from consumer surveys and expert interviews. Results indicate that BNPL application significantly enhances consumer spending capacity by allowing deferred payments, thus maintaining purchasing activity even during financial strains. However, potential risks such as increased consumer debt are also discussed. The study concludes with strategic implications for e-commerce platforms and policymakers, suggesting ways to maximize the benefits of BNPL application while mitigating its drawbacks. This research contributes to a deeper understanding of financial technologies in supporting consumer spending and offers actionable insights for future economic resilience.